JUMLAH TENAGA KERJA KAITANNYA DENGAN HASIL PRODUKSI PADA SEKTOR INDUSTRI KECIL LOGAM - Dian Dewi Roshita, (Pendidikan Ekonomi, 2010)
Small scale industries have been developing rapidly. The crisis in 1997 and global crisis did not bring about great negative impacts on small scale industries. Moreover, small scale industries have survived and accommodated labor. Therefore, to what extent the increase in production was achieved by small scale industries through using labor. This study was associative research. This research was aimed to find out the relationship between the number of labor and result of production in small scale steel industries. It was affirmed that there was positive relationship between the number of labor and result of production in small scale steel industries in Ngingas, Waru, in Sidoarjo municipality.